RESPON GENOTIPE UBI KAYU (Manohot Esculenta Crantz) TERHADAP DOSIS PUPUK KANDANG KOTORAN SAPI TALUK KUANTAN - Herman Herman; Dewi Indriyani Roslim; Ingga Yurisna Fitriani (UIR Press, 2016)
Cassava (Manihot esculenta crantz) is one of the agricultural commoditythat produce tuber for food source in Indonesia. The research objective was to determine the effect of manure on tuber yield and genetic diversity of the five genotypes of cassava Taluk Kuantan. The research was arranged in the randomized block design (RBD) with two factors. The first factor was five cassava genotypes namely: (IY1) cassava pucuk hitam, (IY 2) cassavabangka, (IY3) cassava pulut, (IY4) cassava roti; and (IY5) cassava pucuk hijau. The second factor was the fertilizer of cow manure consists of five doses, namely: P0 (0 kg/plant), P1 (2 kg/plant), P2 (4 kg/plant), P3 (6 kg/plant); and P4 (8 kg/plant). The parameters observed were morphologicaland agronomiccharacters of cassava, such as plant height,number of tubers/plant, tuber diameter, tuber length, and tuber weight/plant. Pulut cassava produced heaviest tuber in the fertilizer with a dose of 4 kg, bangka and pucuk hijau cassavas produced the highest tuber weight in the fertilizer with 6 kg dose.